The construction of a ratiometric dual-emitting amorphous europium-organic frameworks for sensitive detection of water in white spirit. (October 2022) - Dang, Jiaqi; Zhu, Ruifeng; Fang, Wenhui; Hu, Ye; Wu, Ying; Xin, Shixian; Li, Min; Chen, Bozhen; Zhao, Hong; Li, Zengxi
Abstract: It is very crucial to develop a simple and fast-responsive sensor for the detection of water content in organic solvents. Herein, three different europium-organic frameworks (Eu-MOFs): amorphous Eu-2-aminoterephthalic acid (amEu-NH2 BDC), crystalline Eu-2-aminoterephthalic acid (cryEu-NH2 BDC) and amorphous Eu-1, 4-benzenedicarboxylic acid (amEu-BDC) are synthesized, respectively. amEu-NH2 BDC is employed as fluorescence probe for the determination of water in ethanol. Results indicate that amEu-NH2 BDC exhibits good performance due to its dual-wavelength fluorescence (FL) with the ligand (NH2 BDC)-centered blue luminescence at 430 nm and Eu-centered red luminescence at 615 nm. With the increase of water contents in ethanol, the emission intensity at 430 nm increases dramatically, while that at 615 nm decreases under a single excitation at 270 nm. By measuring the ratio of emission intensity at 430 nm and 615 nm (I430 /I615 ), a wide concentration range from 1% to 99.5% water in ethanol is obtained with a lower detection limit value of 0.024% (S/N = 3). Besides, in the presence of water in ethanol, the fluorescence color of amEu-NH2 BDC changes from red to blue under 365 nm UV light. Thus, the visual device for the detection of water is realized by using amEu-NH2 BDC. Combined with the fluorescence lifetime and density functional theory, it is shown that red luminescence weakens due to dynamic quenching and non-radiative vibration energy transfer, and blue luminescence is enhanced due to the hydrogen bonding between water and carboxyl groups in the ligand, which enhances the intramolecular charge transfer process. The proposed method has characteristics of rapid response, excellent stability, high sensitivity and selectivity. Importantly, it can be successfully applied to monitor the content of water in white spirit samples. Graphical abstract: A ratiometric fluorescence approach is established by using a dual-emitting amorphous europium-organic framework of amEu-NH2 BDC for the sensitive and selective detection of water in ethanol. Image 1 Highlights: A novel and simple strategy was employed to synthesize a dual-emission amEu-NH2 BDC. The presence of water in ethanol changed the ratio of the emission intensity between 430 nm and 615 nm of amEu-NH2 BDC under a single excitation at 270 nm. The proposed method was used to specially identify water in ethanol with high sensitivity, selectivity and stability. A visual device for the detection of water was realized by using amEu-NH2 BDC.